State identities and the homogenisation of peoples - Rae, Heather (Cambridge studies in international relations, 2002)
"Why have forced displacement, ethnic cleansing and genocide been an enduring feature of the modern state system? In this ground-breaking book, Heather Rae locates these practices of 'pathological homogenisation' in the processes of state-building. Political elites have repeatedly used available cultural resources to redefine bounded political communities as exclusive moral communities, from which outsiders must be expelled. Showing that these practices predate the age of nationalism, Rae examines cases from both the pre-nationalist and nationalist eras: the expulsion of the Jews from fifteenth-century Spain, the persecution of the Huguenots under Louis XIV and, in the twentieth century, the Armenian genocide and the ethnic cleansing in the former Yugoslavia. She argues that those atrocities have prompted the development of international norms of legitimate state behaviour that increasingly define sovereignty as conditional. Rae concludes by examining two 'threshold' cases - the Czech Republic and Macedonia - to identify the factors that may inhibit pathological homogenisation as a method of state-building."--Jacket